Use of Meet Apps to Improve Student Achievement during the Pandemic - Suyahman, Suyahman; Irfana, Tungga Buana; Touwe, Yohana S; Rohman, Nur; Andika, Alek (World Psychology, 2024)
The use of meet applications is one way that is easily used by educators and students in carrying out the teaching and learning process during a pandemic. The pandemic that haunts the world of education does not demand the possibility to stop studying. Meet which strongly supports students to stay in education. The meet application is a technology system in the form of videos used in a forum, especially in the field of education, which can be used as a substitute for direct teaching and learning due to serious problems. The objectives of this study include 1) making it easier for educators and students to teach 2) reaching long distances 3) knowing the development of students who are indirectly using meet 4) making meet as one of the right solutions during a pandemic. The method used in this case is a quantitative method which does it by directly surveying the destination. The result of this study is how the use of the google meet application for the world of education which can foster high enthusiasm in achieving student achievement during a pandemic. The limitation of this study is that it is difficult for researchers to know the state of students in the online teaching and learning process in using the meet application to support student learning. Researchers hope that the use of meet in the world of education can help students to foster a spirit of creativity during the pandemic.